High-Resolution Pulse Oximetry and Titration of a Mandibular Advancement Device for Obstructive Sleep Apnea - Metz, James E.; Attarian, Hrayr P.; Harrison, Mickey C.; Blank, James E.; Takacs, Christopher M.; Smith, Dale L.; Gozal, David (Frontiers in Neurology, 2019)
Background: To determine whether utilizing high-resolution pulse oximetry is a viable method for evaluating the successful titration of oral appliances for the treatment of obstructive sleep apnea (OSA) patients. Methods: Of 136 consecutive potentially eligible OSA patients, 133 were fitted with mandibular advancement devices (MADs), and 101 completed all phases of treatment. The vertical and horizontal dimensions of the appliances were adjusted based on three-nights with a high-resolution pulse oximeter during sleep and associated software after each adjustment. Results: Significant improvements in OSA severity were apparent in patients at all disease severity levels. High-resolution pulse oximetry provided reliable guidance in the titration process of mandibular advancement therapy. In sixty-seven subjects (66.3%), a respiratory event index of <5 events/hour was achieved. Conclusions: OSA can be effectively treated with a MAD at any severity level, and high-resolution pulse oximetry provides critical information to guide oral appliance titration.